A Study on Quality Work Life in TRIKUT Info Service Private Limited, Coimbatore - Veronicammal, D.; Vimal Raj, L. (Asian Journal of Managerial Science, 2014)
Quality Work Life refers to the favorableness’ or unfavourableness of the job environment of an organization for its employees. It is a generic term which covers a person’s feelings about every dimension of work. To render its versatile services. it expertise in providing solutions by working together with every individual client in A Team to Render the Innovative services by Keenly Understanding their Terms, which has carved a niche for ourselves in the global and Indian markets. Trikut allows the delivery of all these services in one neat package and provides clients the flexibility to staff and de staff as necessary. They are one of the leading professional Recruitment firms and outsourcing company in India. Backed a completely computerized data bank, we successfully provide the employers with our recruitment solution services. This paper explains the quality work life data collected from the employees in TRIKUT, Coimbatore and the analysis of data are presented.